2018
DOI: 10.3390/agriculture8080122
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Marbling Gene Loci in Commercial Pigs in Canadian Herds

Abstract: A genome-wide association study (GWAS) was performed on the intramuscular fat percentage in pork chops in commercially available swine in Canada. The Duroc, Iberian, Lacombe, Berkshire, and Pietrain breeds were crossed with Large White sows, and their F1 offspring were ranked according to the intramuscular fat percentage (IMF %) obtained in their longissimus dorsi (LD) muscle loin chops. The ideal IMF % is considered to be >3%, whereas the average is~1.5% in North American pork. The genetics of the top 10% and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…At present, many studies have shown that IMF content of different breeds varies considerably (Garcia et al, 1986; Davoli et al, 2016). For instance, Chinese indigenous breeds are distinctively high in IMF content compared to main commercial breeds, among which the Duroc breed is the highest (Casellas et al, 2013; Meadus et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At present, many studies have shown that IMF content of different breeds varies considerably (Garcia et al, 1986; Davoli et al, 2016). For instance, Chinese indigenous breeds are distinctively high in IMF content compared to main commercial breeds, among which the Duroc breed is the highest (Casellas et al, 2013; Meadus et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several chromosomal regions (QTLs) and molecular markers (SNPs) are now providing insights into specific candidate gene(s) controlling growth, nutrient uptake, disease resistance, meat quality traits and fat metabolism [ 93 , 105 ]. However, it remains a major challenge to nutritionally sway existing differentially methylated sites where genes involved in lipid metabolism are found [ 118 ].…”
Section: Qtl Regions and Snps For Fat Metabolism And Imf Accretion In Pigsmentioning
confidence: 99%
“…Gene expression tools are often used to study metabolic pathways in farm animals, particularly of IMF. These works are highly valuable for clean meat research, as they are not aimed for regenerative medicine, but rather focus on meat traits, such as marbling (Lee et al, 2010;Sadkowski et al, 2014;Chen et al, 2015;Hudson et al, 2015;Meadus et al, 2018), myogenesis (Wang et al, 2005(Wang et al, , 2015Lee et al, 2014;Dai et al, 2016), and sensory qualities (Bernard et al, 2007;Hocquette et al, 2007;Bongiorni et al, 2016;Tizioto et al, 2016). Research on correlations between gene expression and meat quality has been recently summarized in several publications.…”
Section: Gene Expressionmentioning
confidence: 99%